Application of lhrha and hcg to stimulate spermiation and spawning of the toad, Duttaphrynus melanostictus (Schneider, 1799) - Thu, Do Van; Binh, Doan Viet; Khoi, Tran Xuan; Hue, Le Thi; Ninh, Vo Thi (Academia Journal of Biology, 2014)
In Vietnam, the population of Duttaphrynus melanostictus in the wild has been declined due to overharvesting for snake farms and consumption and environmental pollution. While Black-lipped Toad in cativity rarely ovulates spontaneuosly. Therefore, it’s necessary to study the assisted reproductive techniques to help preserve them. In this study, we used LHRHa and HCG to stimulate induction of spermiation and of spawning of toad. Male were injected with 2 µg/g LHRHa or 3 IU HCG/g to stimulate sperm release. Female were divided in two groups: the first group was administred a single dose of 500 IU HCG (considered as unpriming group) and the second group was administred first two sequential anovulatory dose of 100 IU HCG, repeat after 72 hours. Forty-eight hours after the second injection, the ovulatory dose of 500 IU HCG was injected (priming group). The results showed that injection of LHRHa and HCG stimulates sperm release graetest in time from 5-7 hours after injection. Five hours after injection of LHRHa or HCG, toad sperm concentration was 2.6 and 1.96 million/ml, sperm motility was 82.5 and 85%. Unprimed females failed to spawn any eggs. Whereas, 60% of primed females spawned in the period from 14-16 hours after the last injection of HCG.